2022
DOI: 10.3390/fi14040121
|View full text |Cite
|
Sign up to set email alerts
|

Creating Honeypots to Prevent Online Child Exploitation

Abstract: Honeypots have been a key tool in controlling and understanding digital crime for several decades. The tool has traditionally been deployed against actors who are attempting to hack into systems or as a discovery mechanism for new forms of malware. This paper presents a novel approach to using a honeypot architecture in conjunction with social networks to respond to non-technical digital crimes. The tool is presented within the context of Child Exploitation Material (CEM), and to support the goal of taking an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This provides opportunities for individuals to embed CSAM among legal pornography and this puts the onus on the site owners to identify and take down illegal content. Pornhub (2021) reported that they had identified more than twenty-thousand videos and photos as potential CSAM in one year, representing 0.6 % of the total site content, and that they were taking additional steps to cleanse their site of CSAM (see Scanlan et al, 2024).…”
Section: Offending Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations
“…This provides opportunities for individuals to embed CSAM among legal pornography and this puts the onus on the site owners to identify and take down illegal content. Pornhub (2021) reported that they had identified more than twenty-thousand videos and photos as potential CSAM in one year, representing 0.6 % of the total site content, and that they were taking additional steps to cleanse their site of CSAM (see Scanlan et al, 2024).…”
Section: Offending Pathwaysmentioning
confidence: 99%
“…Our findings suggest that embedded CSAM in legal pornography sites may be particularly problematic as a gateway to offending. It is gratifying to see that some companies (e.g., Pornhub, 2021;Scanlan et al, 2024) are making efforts to screen site content for CSAM, but undoubtedly more could be done across the pornography industry in this regard.…”
Section: Implications For Preventionmentioning
confidence: 99%
See 2 more Smart Citations